Construction and validation of a prediction model of extrahepatic metastasis for hepatocellular carcinoma based on common clinically available data - Zhou, Lliuxin; Zhou, Liuxin; Ren, Li; Qi, Mengjian; Wang, Wen; Su, Xiaoxia; Yin, Fengjiao; Deng, Manjun; Wang, Haijiu; Fan, Haining; Wang, Zhixin (Frontiers in Oncology, 2022)
Abstract Objective：This study aimed to investigate the clinical characteristics and risk factors of patients with primary hepatic carcinoma combined with extrahepatic metastases and establish an effective diagnostic nomogram for extrahepatic metastasis. Methods：Clinical and pathological data of 456 primary hepatic cancer patients admitted to the Affiliated Hospital of Qinghai University between January 2015 and May 2018 were documented. General information, laboratory testsing, tumor imaging characteristics to clarify Clinical risk factors for extrahepatic metastasis of primary hepatic carcinoma. Those screened risks were selected into construct a clinical prediction model using the R. The predictive accuracy and discriminative ability of the model were determined by concordance index(C-index) and calibration curve. The results were validated using bootstrap resampling and 151 patients from June 2018 to December 2019 at the same institution. Results:On multivariate analysis, independent factors for extrahepatic metastasis were neutrophils, prothrombin time, tumor number, tumor size, which were selected into the model. The C-index of the model for predicting extrahepatic metastasis was 0.672. In the validation cohort, the C-index of the model for predicting extrahepatic metastasis was 0.694. In the train cohort and validation cohort, the calibration curve for probability of extrahepatic metastasis showed good agreement between prediction by nomogram and actual observation. Conclusion: The prediction model for extrahepatic metastasis of primary hepatic carcinoma constructed in this study has good evaluation ability.Using the model, the missed diagnosis rate of extrahepatic metastasis can be reduced.